Inter-American Standards on Business and Human Rights. State Obligations Regarding the Rights of Children - Castillo Aguirre, David Mauricio (Iuris Dictio, 2022)
In this globalized world, the American States face a challenge: to find the balance between the economic development and the exercise of human rights, including the fulfillment of the state and non-state actors"™ obligations. This article analyses children human rights in the context of the report of Inter-American standards on business and human rights. For these purposes, it shows the evolution of international instruments on human rights and companies "”both in the universal and in the Inter-American system"”, to then explore the report, with special emphasis on the development of the obligations to respect, fulfil and protect human rights. Finally, it reflects on the human rights situation of children regarding business activities and makes conclusions.